Токсиколого-гигиеническая оценка биодеградируемых биоактивных накостных пластин для остеосинтеза - Галатенко, Н.А.; Маланчук, В.А.; Астапенко, Е.А.; Рожнова, Р.А.; Куксин, А.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
Complex toxicological-hygienic studies of biodestructive bone miniplate samples for osteosynthesis composed of polyurethane co-polymer with epoxide hydroxyapatite and immunomodulator (levamisole-containing olygomer) are carried out. The results indicate the safety of the developed bone miniplate material, which allows us to recommend its usage as a fixing device for fractured bone fragments in oral and maxillofacial surgery.